2019
DOI: 10.1111/1756-185x.13697
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and risk factors for gout attacks during anti‐tuberculosis treatment: A case‐control study in South Korea

Abstract: Aim This study aimed to investigate the clinical features and risk factors of gout attacks during anti‐tuberculosis (TB) treatment in South Korea. Method We investigated the clinical characteristics of 49 patients who suffered from gout attacks while taking anti‐TB medications. Among them, 25 TB patients having newly developed gout attacks without prior history of gout were set to the gout group. Seventy‐five age‐ and sex‐matched TB patients without gout attacks during anti‐TB therapy were randomly selected as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
(58 reference statements)
0
9
0
Order By: Relevance
“…Our study found that intravenous administration significantly increased plasma concentrations compared with oral administration, which may be attributed to the effect of food and the firstpass effect of the liver (21). A large number of previous studies have shown that anti-TB drugs can affect uric acid metabolism in humans, which could result in elevated blood uric acid (22)(23)(24). The mechanisms of the interaction between blood uric acid and anti-TB drug metabolism need to be further investigated.…”
Section: Factors Influencing the Plasma Concentration Of Anti-tb Drugsmentioning
confidence: 55%
“…Our study found that intravenous administration significantly increased plasma concentrations compared with oral administration, which may be attributed to the effect of food and the firstpass effect of the liver (21). A large number of previous studies have shown that anti-TB drugs can affect uric acid metabolism in humans, which could result in elevated blood uric acid (22)(23)(24). The mechanisms of the interaction between blood uric acid and anti-TB drug metabolism need to be further investigated.…”
Section: Factors Influencing the Plasma Concentration Of Anti-tb Drugsmentioning
confidence: 55%
“…In one group of high-risk patients, the mean AE SD sU level was increased to 8.4AE3.1 mg/dL (P<.001) at 2 months from pretreatment levels of 5.5AE1.9 mg/dL. 100 Mean AE SD time from treatment initiation to gouty attack was 4.13AE4 months, and half of the attacks occurred during the first 2 months of treatment. 100 Anti-inflammatories and Immunosuppressives Low-Dose Aspirin.…”
Section: Antihypertensivesmentioning
confidence: 87%
“…100 Mean AE SD time from treatment initiation to gouty attack was 4.13AE4 months, and half of the attacks occurred during the first 2 months of treatment. 100 Anti-inflammatories and Immunosuppressives Low-Dose Aspirin. As noted previously herein, low doses of aspirin and other salicylates may raise sU levels by promoting renal UA reabsorption.…”
Section: Antihypertensivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, due to a paradigm shift in the TB treatment field towards HDTs by repurposing immunomodulatory drugs to combat TB (Fatima et al, 2021), novel treatment approaches focusing on host‐originated anti‐Mtb activities with FDA‐approved safe drugs have gained increased interest (Ramakrishnan et al, 2015). Based on the development of gout attacks while taking anti‐TB drugs (Ha et al, 2019) and recent evidence of employment of colchicine to improve outcomes of infectious diseases and other inflammatory diseases (Hariyanto et al, 2021; Vaidya et al, 2021), as well as its inconclusive roles in immunological actions on TB, to the best of our knowledge, we show here for the first time the positive effect of colchicine on controlling Mtb infection in macrophages and in vivo. Surprisingly, the underlying mechanism of colchicine, unlike its commonly reported role in the suppression of NLRP3 and IL‐1β secretion, is associated with enhancing the anti‐Mtb activities of macrophages through the reinforcement of IL‐1β signalling and high‐level PGE 2 production.…”
Section: Introductionmentioning
confidence: 99%